2021
DOI: 10.2116/analsci.20sar05
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Proteins Adsorbed at Nanoporous Materials

Abstract: A nanoporous material has been applied for the development of functional nanobiomaterials by utilizing its uniform pore structure and large adsorption capacity. The structure and stability of biomacromolecules, such as peptide, oligonucleotide, and protein, are primary factors to govern the performance of nanobiomaterials, so that their direct characterization methodologies are in progress. In this review, we focus on recent topics in the structural characterization of protein molecules adsorbed at a nanoporou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 120 publications
(269 reference statements)
0
3
0
Order By: Relevance
“…This results are in agreement with recent publication on myoglobin infiltration and condensation at pores entrance. 13,60 Results of infiltration of glutaminase and amino acid oxidase show an increased overlayer deposition close to the enzyme diameter. In case of urase the infiltration into the structure seems to be hindered and an overlayer thickness similar in value to the enzyme diameter was measured.…”
Section: Resultsmentioning
confidence: 99%
“…This results are in agreement with recent publication on myoglobin infiltration and condensation at pores entrance. 13,60 Results of infiltration of glutaminase and amino acid oxidase show an increased overlayer deposition close to the enzyme diameter. In case of urase the infiltration into the structure seems to be hindered and an overlayer thickness similar in value to the enzyme diameter was measured.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, porous solids are often used as supports in order to achieve high surface areas, sometimes even to retain big molecular discrete catalysts, enzymes in particular, within the solid to minimize leaching, but those pores may impose geometrical constrains on the ability of molecular catalysts to adopt their required structure and interact with the reactants for optimum promotion of reactions, especially with large molecular catalysts such as enzymes (as mentioned before, Section ). , To the specific limitations imposed by the local structure of the pores, additional consideration needs to be given to mass transport limitations of reactants and products to and from the catalytic site, although this is a problem common to all heterogeneous catalysts. It should be mentioned that the complexity of solid surfaces can also provide unique opportunities, since they can display large atomic assemblies difficult to reproduce via molecular synthesis.…”
Section: Immobilization Of Homogeneous Catalysts On Surfacesmentioning
confidence: 99%
“…Cylindrical nanopores have been applied in the development of artificial biocatalytic systems, controlled drug release systems, artificial chaperones, and solid-state nanopore sensing devices . Because the conformation of a biomacromolecule, such as protein or DNA, is sensitive to its microenvironment and surface interactions at the pore wall, its correlation with the nanopore diameter is a key issue in such nanopore-based technologies. The folding/unfolding properties of a monomeric biomacromolecule are an important part of conformational studies, and optimal nanopore diameters have been reported for enhancing the stability of the folded structures and the molecular chaperoning function of biomacromolecules …”
mentioning
confidence: 99%